Allelic Frequency of Kappa-Casein Locus (Asp148/Ala) in F1: Simmental (Bos taurus) x Ongole Grade (Bos indicus) - M A Mu'in; A Supriyantono (Media Peternakan, 2012)
This study was conducted to detect the genetic variants (single nucleotide polymorphism) of kappa-casein locus (Asp148/Ala) in F1: Simmental (Bos taurus) x Ongole grade (Bos indicus), SIMPO. Genomic DNA was isolated from blood sample of 40 SIMPO (21 males and 19 females). A 780 bp specific fragment of kappa-casein gene spanning from the forth exon region (517 bp) to forth intron (263 bp) was successfully amplified. The result of the PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphisms) analysis using HindIII enzyme showed that two genotypes (AA and AB) were found at this locus in SIMPO. The frequencies of A and B alleles in SIMPO were 0.79 and 0.21, respectively. The frequency lies between B. taurus (Simmental) and B. indicus group.